PEMBINAAN IMPELEMENTASI MODERASI BERAGAMA OLEH PEMBINA KEPADA GURU RAUDHATUL ATHFAL ISLAM TERPADU AL YAMAN KECAMATAN LUBUK SIKAPING KABUPATEN PASAMAN - Farina, Dahlia; Aguswan, Aguswan; Rahmi, Rahmi (Ensiklopedia of Journal, 2025)
This study aims to analyze the role of supervisor coaching for teachers in planning, implementing and evaluating the implementation of religious moderation in the Raudhatul Athfal Islam Terpadu (RAIT Al YAMAN) environment. The results of the study indicate that supervisor coaching in planning the implementation of religious moderation is realized in the form of: guidance, internalization and integration of religious moderation values, coaching, motivation and workshops. While supervisor coaching in the field of implementation is realized in the form of: supervision, monitoring, mentoring, direction, coordination and evaluation. While the role of supervisor coaching in the field of evaluation is to help teachers compile indicators for evaluating religious moderation, provide direction in compiling evaluation instruments, conduct observations with teachers, help teachers collect learning data and compile evaluation reports, compile follow-up plans based on evaluation results and identify students who need mentoring, provide feedback on student evaluations and conduct training on evaluating religious moderation.Keywords: Guidance, Supervision, Religious Moderation.